Peran Strategis Sumber Daya Manusia dalam Menggerakkan Inovasi Kewirausahaan Perusahaan - Hesti Kusumaningrum; Shalwa Azzahra; Azma Auliya Rifqiya (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Innovation and entrepreneurship are vital factors in spurring company progress in the era of competitive globalization. Rapid changes in technology, markets, and consumer needs emphasize the need for companies to continually adapt and evolve. In the context of increasingly fierce competition, innovation is the main key that differentiates between growing and stagnant companies. Entrepreneurship brings a broader concept of turning creative ideas into real business opportunities. Although awareness of the importance of innovation and entrepreneurship is increasing, there are still a number of challenges that must be overcome in implementing these concepts effectively in Indonesia. Overall, companies that are successful in managing innovation and developing entrepreneurship have several key factors that support their success. A strong innovation culture, high management support, and employee involvement in the innovation process are very important elements to be accepted by companies to improve innovative and entrepreneurial performance.